The janitor's boy - Clements, Andrew, 1949- (New York : Aladdin Paperbacks, 2001)
Fifth grader Jack finds himself the target of ridicule at school when it becomes known that his father is one of the janitors, and he turns his anger onto his father.
Book Links (A.L.A.)
School Library Journal
Wilson's Children
5.7
3-6
3-6.
Keywords: Fathers and sons -- Fiction; Janitors -- Fiction; Schools -- Fiction